The Road to Poverty Reduction: Corporate Governance and Female Participation in MFIs - Gudjonsson, Sigurdur <1976> (Alma Mater Studiorum - Università di Bologna, 2015)
1.Microfinance Industry – Context of Analysis. This paper is an introduction to the microfinance industry. It serves as a context of analysis, for the empirical settings and basis for building the theoretical argument for the thesis. 2.Women in Microfinance Institutions: The Road to Poverty Reduction and Gender Equality? One of the unique aspects of microfinance institutions is their focus on outreach, i.e. their ability to reach the poor. This paper explores whether the presence of women in microfinance institutions is associated with improved outreach. Building on prior research that shows that women tend to improve financial performance and social responsibility, we examine an original dataset of 226 microfinance institutions. The empirical results suggest that the presence of a female CEO, female managers and female loan officers is directly related to improved outreach, while the presence of women board members is not. 3. Women in Microfinance Institutions: Is There a Trade-Off Between Outreach and Sustainability? Abstract This paper’s contribution to the understanding of microfinance is two-fold. First, while it has been shown that female CEOs in MFIs increase financial performance, it will be argued that female managers, female loan officers and female board members will do the same. Secondly, having previously shown that having a female presence in management in MFIs improves social performance the outreach, it will be argued that having females in the MFIs’ management will not lead to a trade-off between outreach and sustainability. These findings are based on an original data set of 226 MFIs. Statistical analysis demonstrates that a weak relationship between female managers and female loan officers vis-à-vis financial performance, but female board members do not. The trade-off between outreach and sustainability can be avoided with the appointment of females to the MFIs’ management positions, but the same cannot be concluded for female board members.